Tympanostomy tube otorrhea in children: prevention and treatment - van Dongen, Thijs M A; Damoiseaux, Roger A M J; Schilder, Anne G M (Current opinion in otolaryngology & head and neck surgery, 2018)
One in two children treated with tympanostomy tubes, experience episodes of otorrhea whilst their tubes are in place. In this review, we present the results of the most recent publications on prevention and treatment of tympanostomy tube otorrhea (TTO). Recent systematic reviews on water precautions for children with tympanostomy tubes support the American Academy of Otolaryngology - Head and Neck Surgery guideline recommendation against such preventive measures as there is no evidence that it protects against TTO. Studies on tympanostomy tube design and material suggest that silicone tubes have a lower TTO risk and that biofilms appear to be mainly located in the perpendicular junction of the T-tubes and the round rims of the Paparella-type tubes. Another study shows that the biofilm-component DNAB-II protein is present in otorrhea of half of children with TTO. Targeting this protein could lead to a collapse of the biofilm structure and as such a potential new treatment for chronic TTO. New systematic reviews show that antibiotic eardrops are the most effective first-line treatment of acute TTO and suggest that an antibiotic-corticosteroid combination is more effective than antibiotic only. Although in many countries, quinolone eardrops are the preferred choice because of being non-ototoxic, one study found a higher risk of persistent perforation after tube extrusion in children treated with quinolone eardrops as compared with children treated with aminoglycoside eardrops. Recent evidence confirms that water precautions for children with tympanostomy tubes are not effective in preventing TTO. Antibiotic-corticosteroid eardrops are the most effective treatment of acute TTO.